THE EVOLUTION OF RIGHT TO INFORMATION IN INDIA: A CONSTITUTIONAL AND LEGISLATIVE ANALYSIS - Pantawane, Jayashree; Butle , Abhay (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Right to Information (RTI) in India has emerged as a cornerstone of democracy, enabling citizens to actively participate in governance and hold authorities accountable. This study examines the evolution of the RTI framework in India, tracing its constitutional, legislative, and judicial milestones. By analyzing the socio-political dynamics that shaped its development, this research provides a comprehensive understanding of the RTI Act’s implications, successes, and challenges. The study highlights the transformative role of RTI in promoting transparency, combating corruption, and fostering good governance while addressing barriers such as bureaucratic resistance and misuse of the law. Recommendations for enhancing the efficacy of the RTI mechanism are also provided.